Determination of the chromosome aberrations frequency and the dynamics of acrocentric chromosomes associations in children with type I diabetes - Yeromenko, R. F.; Kovalova, V. I.; Lytvynova, O. M.; Palamarchuk, O. O.; Lytvynov, V. S. (Zaporozhye Medical Journal, 2018)
To date, it’s known that in Ukraine there are about 1 million patients with diabetes, but their real number is 2–3 times more, since this disease is usually diagnosed at the stage of already manifested pathological process. Unfortunately, diabetes mellitus remains an incurable disease, but it is possible to prolong life of patients or improve its quality by preventing or delaying its complications. Objective. To study quantitative and qualitative cytogenetic indices in peripheral blood lymphocytes of children with type 1 diabetes mellitus. Materials and methods. Cytogenetic study was performed in 30 children with type 1 diabetes aged from 5 to 17 years and 40 practically healthy peers. Associations of acrocentric chromosomes (AAX) were evaluated using criteria developed by K. D. Zang and E. Back (1968). Metaphase plate analysis was performed using a Leica Galen III binocular microscope (Austria), an eyepiece of ×15, a lens of ×100, a binocular nozzle of ×1.25. The statistical processing of the results was carried out using Excel application packages, SPSS Statistica17.0. Results: Changes in the somatic cells genome stability of children with type 1 diabetes have been revealed. Thus, the spontaneous level of chromosomal aberrations in the main and control groups was within 3.66 % and 0.96 %, respectively, and significantly exceeded the control indices (P < 0.005). In children, genomic abnormalities in the form of polyploidy and hypoploidy, as well as a decrease in CL0+2, were found, which indicates a decrease in the immunoreactivity of the sick children organism and allows to consider them as persons with secondary immunodeficiency. Conclusions: The spontaneous level of chromosomal aberrations in peripheral blood lymphocytes in children with type 1 diabetes significantly exceeded the control indices. Cytogenetic examination of children with type 1 diabetes has revealed genomic disorders in the form of polyploid cells, which have not been detected in the control group. Changes in the genome stability in the form of hypoploid aneuploidy have also been found in the examined group. In children with type 1 diabetes a decrease in the acrocentric chromosomes ability to join associations has been identified, which makes it possible to consider these children as persons with secondary immunodeficiency.